USE OF BIODEGRADABLE MATERIALS AS A DIDACTIC RESOURCE IN SURGICAL PRACTICE IN DENTISTRY - Freires, Rafael Alves; de Aguiar, Guilherme Brito; Ramos, Eder da Silva; Paulo, Thiago da Silva; de Sousa, Leonardo Gomes; Lopes, Naiara Coelho; Brito, Marcus Vinicius Henriques (Seven Editora, 2025)
The use of biodegradable materials, such as bovine tongue and pig mandible, has emerged as an effective didactic strategy for teaching surgical practices in Dentistry. This paper presents an integrative literature review aimed at analyzing the effectiveness of these materials in students’ technical training. Five studies published between 2008 and 2017 were included, selected from sources such as ABENO Journal, RCBC, and others. Results show that alternative models provide a tactile and visual experience similar to clinical reality, promoting safe and effective learning. It is concluded that biodegradable materials represent an economically viable, accessible, and technically appropriate option for surgical simulation, and their broader use in health education is recommended.DOI: https://doi.org/10.56238/sevened2025.029-011